P31 Differences in distribution of plantar skin rash of secondary syphilis and keratoderma blenorrhagica. (18th May 2015) - Boylan, Johnny; Greenhouse, Peter
Abstract : Background/introduction: Textbooks commonly assert that the most important cause of plantar skin rash is secondary syphilis (2°Syph), but there are many other possible differentials, the principal alternative STI diagnosis being keratoderma blenorrhagica (KB). Aim(s)/objectives: Observational study to quantify differences in distribution and character of plantar rash caused by 2°Syph or KB. Methods: We sourced colour photographs of confirmed 2°Syph and KB from personal slide collections, illustrated textbooks and online academic websites, checked for evidence of correct diagnosis and showing at least 80% of the full plantar surface. Lesion distribution was categorised between either the weightbearing ball and heel or non-weightbearing arch of the foot with gradations shown in the Table 1. Results: We found 50 images of 2°Syph and 25 of KB with reliably attributable clinical diagnoses. The overwhelming majority of 2°Syph lesions were entirely or almost entirely (42/50) confined to the non-weightbearing arch of the foot: Conversely KS lesions were almost all (18/25) distributed over the thicker weightbearing areas. Discussion/conclusion: The plantar rash of 2°Syph is probably seen mostly in thinner areas of arch-of-foot epithelium because vasculitis is hidden under the thickly keratinised weightbearing sole. Any rash covering both areas must raise the possibility of an alternative or double diagnosis or an especially florid presentation.